2004
DOI: 10.1088/0953-8984/16/40/010
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scale thin film investigations with slow polarized muons

Abstract: Muons with 100% spin polarization and whose energy can be continuously varied from 0.5 to 30 keV provide a novel extension of the µSR technique allowing depth dependent studies of thin films and multilayered structures in the range from ∼1 to ∼200 nm. For example it is possible to study magnetic field profiles near the surface of superconductors and directly determine fundamental quantities such as the magnetic penetration depth. Low energy muons (LE-µ + ) also allow mapping the spin polarization in multilayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 64 publications
1
87
0
Order By: Relevance
“…Interestingly, the development of variable-energy slow-μ + beams [17] has recently enabled μ + SR to profile penetration of weak magnetic fields at the surface of YBa 2 Cu 3 O 6.92 (state-of-the-art high quality crystals) [18]. It was found that a dead surface layer (about 10% of λ) was needed to model λ with Meissner-state theory (similar anomalies were found in previous studies [19,20]). These low-energy μ + SR profiling results indicate that interpretation of surface-specific measurements of λ is less direct than presumed (as discussed further in section 5.4), making the understanding of bulk μ + SR measurements of λ all that more imperative.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly, the development of variable-energy slow-μ + beams [17] has recently enabled μ + SR to profile penetration of weak magnetic fields at the surface of YBa 2 Cu 3 O 6.92 (state-of-the-art high quality crystals) [18]. It was found that a dead surface layer (about 10% of λ) was needed to model λ with Meissner-state theory (similar anomalies were found in previous studies [19,20]). These low-energy μ + SR profiling results indicate that interpretation of surface-specific measurements of λ is less direct than presumed (as discussed further in section 5.4), making the understanding of bulk μ + SR measurements of λ all that more imperative.…”
Section: Introductionsupporting
confidence: 55%
“…The low-energy  + SR method is particularly suited for obtaining detailed depth profiles of static magnetic flux penetration in weak applied magnetic fields [18][19][20]. Shown in figure 8 figure 3), respectively, in [18].…”
Section: Magnetic Field Penetration At Superconductor Surfacesmentioning
confidence: 99%
“…The appearance of Polarized Neutron Reflectometry (PNR) 14,15 and Low-Energy Muon Spin Rotation spectroscopy (LE-µSR) 16,17 techniques qualitatively changed the landscape of studies of surface magnetization. In particular, these techniques enable direct measurements of B(z).…”
Section: Introductionmentioning
confidence: 99%
“…More details on μSR techniques, in general, and LE-μSR, in particular, can be found in Refs. [17][18][19].…”
Section: Methodsmentioning
confidence: 99%